Still figures: Photography, modernity and gender in Neera's Fotografie matrimoniali. - Valisa, Silvia (Italianist)
The article examines the photographic metaphor of the text at a formal and thematic level in the context of Italian modernization. It argues that Anna Radius Zuccari's, known as Neera, use of photography as a ‘new' structural device ultimately frames the novel's protagonist within a very conservative modernity, especially in terms of gender roles.